Biodegradation of Beta-Blockers and Fluoxetine followed by a Chiral HPLC-FD - Ribeiro, Ana R. (2013)
Despite of the massive publications concerning pharmaceuticals in the environment, the problematic related with chiral compounds and enantioselective degradation are still largely unknown [1]. Enantiomers have different interactions with enzymes, receptors and other chiral molecules, leading to different biological activities. Thus, biodegradation tends to be enantioselective in contrast to abiotic degradation. However, biodegradation studies regarding enantioselectivity on the process are scarce [2].] MATERIALS AND METHODS [Four beta-blockers: alprenolol (ALP), propranolol (PHO), metoprolol (MET) and atenolol (ATE) and the antidepressant fluoxetine (FX) were enantiomerically separated by a macrocyclic antibiotic vancomycin CSP (ASTEC Chirobiotic V 5µm) under polar organic mode phase (methanol:ethanol:triethylamine:acetic acid.50:50 v/v) and fluorescence detection for enantiomeric fraction quantification. The developed methods were established using a minimal medium inoculated with activated sludge (AS) as a matrix.] RESULTS AND DISCUSSION [The Chirobiotic VTM was able to resolve ALP and PHO as well as MET, ATE and FX in two short runs. A separation factor (α) between 1.12 and 1.34 and resolution (Rs) between 1.30 and 4.35 were obtained. The methods demonstrated to be selective and linear within the range, with detection limits between 2.5 and 10ng/mL. These methods were applied to follow the biodegradation of the target compounds. The biodegradation assays were performed using AS from a municipal WWTP and the results indicate the higher degradation extents for the S- enantiomer forms at initial concentrations tenfold above those found in the environment (10ppm and 5ppm). The same assays were performed at an initial concentration of 1ppm for a singly supplementation and at 0,5ppm for a mixture of compounds, a closer situation to the real environment.] CONCLUSIONS [To our knowledge, chromatographic enantioseparations of the mixture of ALP and PHO and the mixture of MET, FX and ATE using the Chirobiotic™ V, have not been previously reported. The feasibility of this application was confirmed by two biodegradation studies using AS, with S-form being faster degraded, showing stereoselectivity.